Bioprocess development to enhance biomass and lutein production from Chlorella sorokiniana Kh12. (February 2023) - Vadrale, Akash Pralhad; Dong, Cheng-Di; Haldar, Dibyajyoti; Wu, Chien-Hui; Chen, Chiu-Wen; Singhania, Reeta Rani; Patel, Anil Kumar
Graphical abstract: Highlights: Microalgae isolate Chlorella sorokiniana Kh12 identified as high lutein-producer. Maximum lutein content obtained 17.3 mg/g, one of the best yields reported so far. 3X nutrients offered the maximum lutein yield (65.74 mg/L) under mixotrophy. Effect of temperature 30 °C was second best parameter for high lutein production. 10 k lux was determined the best light condition for biomass and lipid production. Abstract: Present study focused on optimizing bioprocess condition for microalgal lutein production. From previous baseline yields of biomass (3.46 g/L) and lutein (13.7 mg/g), this study examined few key parameters. The 3X:3X ratio macro- and micronutrients was the most affecting parameter with highest biomass and lutein yields of 4.61 g/L and 14.3 mg/g. Temperature 30 °C enhanced the lutein up to 17.3 mg/g but reduced the biomass to 3 g/L. The light effects study showed 10 k lux was most effective for lutein up to 14 mg/g, and effect of increasing salinity (25–75 %) was detrimental. All the above parameters' optimization resulted in a lipid content of 22.5–26.5 %. A maximum lutein productivity and yield of 0.451 mg/L/d and 65.74 mg/L with a 3X:3X macro- and micronutrient ratio was achieved. The Chlorella sorokiniana Kh12 strain exhibited one of the highest yields among recent reports; hence it could be a source for commercial lutein production.